PENYUSUNAN COMPOSITE LEADING INDICATOR SIKLUS BISNIS DI INDONESIA MENGGUNAKAN ARTIFICIAL NEURAL NETWORK - Dwiyoso, Hertoto; Susilo, Yohanes Hadi (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2007)
After the 1997 financial crisis, like many developing Asian countries, Indonesiahave taken major initiatives to improve their national statistical systems as part oftheir efforts in strengthening national economic monitoring and surveilance andcrisis prevention measure. Composite leading indicators are becoming more widelyrecognized in predicting business cycles in Indonesia.This article attemps to construct composite leading indicators of business cycles inIndonesia using monthly economic and financial data during the sample period of1970–2001. This article also explore the possibility of constructing compositeleading indicators of business cycles by using artificial neural network method. Theresult show that the composite leading indicators constructed by artificial neuralnetwork method is able to predict all of the turning points of business cycles inIndonesia. The performance of this method is comparable to the other predictionmethod such as regression.Keywords: Aggregate economic activity, business cycles, artificial neural network,predicting, composite leading indicators, turning points